Factors Affecting Compliance Community In Implementing The Health Protocol Program During The Covid-19 Pandemic In Sempor Hamlet, Pujotirto Village, Kebumen Regency - Utomo, Aji; Santoso, Dadi; Septiwi, Cahyu (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
COVID-19 cases reached 147.8 million, while the data in Indonesia that had been confirmed positive was 1.64 million cases. The government programs that are being promoted are, “3M, namely wearing masks, washing hands, and avoiding crowds. During the implementation of health protocols during this pandemic, there are still some people who do not comply, this can be caused by many things. That the factors that influence compliance include knowledge, motivation and family support. Objective: aims to determine the factors that affect community compliance in implementing the Health Protocol during the COVID-19 pandemic in Sempor Hamlet, Pujotirto Village, Kebumen Regency. Methods: The design used is quantitative research which is descriptive analytic. By using a cross-sectional approach. The population in this study were residents of Sempor hamlet, amounting to 573 people with a total sample of 100 people using the Slovin formula. Data analysis using Chi Square test. Results: The results showed that there are two factors that have a significant relationship with community compliance with family support health protocols (p-value 0.009), level of motivation (p-value 0.006). While the level of knowledge has no relationship with compliance (p-value 0.359). Conclusion: Based on these results, it shows that there are several factors that can affect a person's compliance in running a program